ANALISIS EVALUASI PENERAPAN PROGRAM HOME CARE PASIEN PPOK LANSIA PADA MASA NEW NORMAL DI WILAYAH KERJA PUSKESMAS KAUDITAN KABUPATEN MINAHASA UTARA - Koropit, Sesca Vanda; Wasliati, Balqis; Lubis, Basyariah (NHM PRESS, 2023)
Service implementation long ago at the Health Center, home care was first offered. nevertheless, given that services existhomecare The effectiveness of servicehomecare has never been assessed. The purpose of this study is to evaluate the deployment of home care services for elderly COPD patients at the Health Center. The in-depth interview method is being used in this qualitative descriptive study. Data collecting methods included interviewing, observing, and using documentation from the home care audited public health center. The study's findings point to the need for an evaluation of home care services based on inputs that support and are necessary for doing so, such as more officers needed for the health workforce and infrastructure connected to medicines that has to be built. Home care evaluation based on process is the implementation that must be done to improve the achievement of the goals that have been set through organization, communication, competence, recording, and reporting in the implementation of home care services. Evaluation home care based on output (output) is the need to increase achievement in the implementation of previous home care services. As for advice on what infrastructure and equipment are required for home care services, such as medications. Prioritize response time, be more prompt when performing visits, and always be available if an emergency arises that needs to be handled right away